Child-Friendly Justice – Romanian Perspective - Fegyveresi, Zsolt (Child-Friendly Justice. The Participation and the Rights of the Child in Court Proceedings From a Central European Comparative Perspective, 2025)
Abstract:Given that children can also be involved in various civil, administrative and criminal proceedings, it is very important that there are legal instruments in place in each state to guarantee their rights in such situations. Children’s right to participation is a fundamental principle that gives them the opportunity to express their views and have a say in their lives. They must have the opportunity to receive the information necessary and relevant to them in order to form and express their views. In addition to the child’s right to take part in decisions, the right to participation also includes the right to involvement, action or information. This right is closely linked to the child’s development and maturation process. Romanian legislation in line with the Convention on the Rights of the Child ensures that children who are capable of discernment have the right to freely express their opinion on any issue that concerns them not only in their daily life, but also in moments that are less comfortable for them, such as administrative or judicial proceedings. Keywords: child-friendly justice, the right to participate, special protection measure, juvenile justice, hearing of the minor